Economic Freedom and Cross‐Border Acquisitions from Emerging Markets into Developed Economies. (15th September 2016) - Zhang, Jianhong; He, Xinming; van Gorp, Désirée M.
Abstract : Extending the home base perspective by considering investors' parent countries, this study examines the effect of economic freedom (EF) on emerging‐market enterprises' (EMEs) overseas acquisition completion in developed countries. Using a large data set of 5, 174 cross‐border acquisition deals from ten major emerging markets (EMs) during 1985–2011, we find that (1) the probability of deal completion is positively associated with the levels of EF of the acquirers' countries, the acquirers' parent and the target; (2) the EF of the countries of acquirers' parents has a substitutive effect on that of the acquirers' countries; (3) the difference of EF between the targets' countries and the countries of acquirers' parents negatively influences deal completion; and (4) the difference of EF between the targets' countries and the acquirers' countries negatively influences deal completion. These findings have important theoretical implications for international business scholars, as well as practical implications for managers and for policymakers of EMEs that are active in foreign direct investment. © 2016 Wiley Periodicals, Inc .